2020
DOI: 10.1371/journal.pone.0234714
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic hyperplasia: Vascularization, hemodynamic and hormonal analysis of dogs treated with finasteride or orchiectomy

Abstract: As a consequence of a hormonal imbalance, Prostatic Hyperplasia (PH) is characterized by increased prostate volume, along with higher local angiogenesis and vascularization. Orchiectomy is the common treatment for dogs, however it is not an option for breeding animals. Thus, finasteride arises as the drug of choice for stud dogs. Therefore, the aim of this study was to evaluate the effects of orchiectomy or finasteride therapies on hormonal and vascular dynamics of PH dogs. Fifteen dogs, aged 6-13 years were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Hypoxia plays a critical role in shaping the genomic and evolutionary landscapes of cancer ( Bhandari et al, 2020 ; Zhang X. et al, 2020 ), with a multifaceted interplay between hormones, growth factors, and hypoxia in a tumor microenvironment milieu ( Lappano et al, 2022 ), including the HIFs ( Satija et al, 2021 ; Sebestyén et al, 2021 ) and transforming growth factor (TGF-β) produced in the hypoxic, chronic inflammatory settings ( Mortezaee and Majidpoor, 2022 ). Androgen deficiency/deprivation caused drastic endothelial dysfunction, resulting in reduced blood flow (ischemia/hypovascularity) to the prostate gland ( Angrimani et al, 2020 ; Jin Cho and Pyo, 2020 ; Yoon et al, 2020 ), causing an ischemia–hypoxia stress tissue microenvironment ( Thurmond et al, 2015 ; Byrne et al, 2016 ). Hypoxia stress caused the induction of amyloidosis-autophagy-EMT cell signaling interactions, beginning with amyloidosis ( Cheboub et al, 2019 ; Phua, 2021 ) to allow cells to enter a dormant/resting stage ( Audas et al, 2016 ; Mizejewski, 2017 ; Pavliukeviciene et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia plays a critical role in shaping the genomic and evolutionary landscapes of cancer ( Bhandari et al, 2020 ; Zhang X. et al, 2020 ), with a multifaceted interplay between hormones, growth factors, and hypoxia in a tumor microenvironment milieu ( Lappano et al, 2022 ), including the HIFs ( Satija et al, 2021 ; Sebestyén et al, 2021 ) and transforming growth factor (TGF-β) produced in the hypoxic, chronic inflammatory settings ( Mortezaee and Majidpoor, 2022 ). Androgen deficiency/deprivation caused drastic endothelial dysfunction, resulting in reduced blood flow (ischemia/hypovascularity) to the prostate gland ( Angrimani et al, 2020 ; Jin Cho and Pyo, 2020 ; Yoon et al, 2020 ), causing an ischemia–hypoxia stress tissue microenvironment ( Thurmond et al, 2015 ; Byrne et al, 2016 ). Hypoxia stress caused the induction of amyloidosis-autophagy-EMT cell signaling interactions, beginning with amyloidosis ( Cheboub et al, 2019 ; Phua, 2021 ) to allow cells to enter a dormant/resting stage ( Audas et al, 2016 ; Mizejewski, 2017 ; Pavliukeviciene et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-androgenic therapeutics imply nitric oxide downregulation and are known to cause reductions in hemodynamics ( Angrimani et al, 2020 ; Yoon et al, 2020 ), microvascular density (hypovascularity) ( Hochberg et al, 2002 ; Donohue et al, 2005 ; Khwaja et al, 2016 ; Sun et al, 2018 ; Khera et al, 2020 ), and inflammation ( Saylor et al, 2012 ; Hoogland et al, 2021 ; Nazha and Bilen, 2021 ). Finasteride-related anti-androgenic therapy is associated with an increased risk of higher-grade prostate cancer ( Scailteux et al, 2019 ; Hu et al, 2020 ), erectile dysfunction ( Fertig et al, 2017 ), and the post-finasteride syndrome of adverse side effects ( Gupta M. A. et al, 2020 ; Diviccaro et al, 2020 ; Traish, 2020 ; Howell et al, 2021 ; Saengmearnuparp et al, 2021 ).…”
Section: Middle-aging Hypovascularity Hypoxia Hypothesis Patternsmentioning
confidence: 99%
“…Experimental testosterone deprivation orchiectomy studies showed induced changes to the prostate of rats, and testosterone replacement therapy was effective in reversing such alterations [294]. In two 60-day studies, canine orchiectomy lowered prostate vascularisation [295] and blood volume [296].…”
Section: Preventionmentioning
confidence: 97%
“…For the medical treatment of BPH, drugs that reduce prostatic enlargement and hormonal imbalance are preconized. For such purpose, finasteride is the drug of choice for breeding dogs, by leading to reduction in prostatic volume and blood supply (6) and maintaining semen quality and testicular integrity even after two months of treatment (2,13). Finasteride is a 5α-reductase inhibitor, which decreases 70% of circulating dihydrotestosterone (DHT) levels (14).…”
Section: Introductionmentioning
confidence: 99%
“…In a reproductive point of view, BPH is marked by prostate enlargement with significant sperm alterations, such as DNA fragmentation ( 3 , 6 ), motility kinetics ( 2 ), oxidative stress status ( 5 ) and high percentage of sperm defects ( 2 ). The causes under BPH altered sperm features are related to a remarkable hormonal imbalance, affecting both spermatogenesis and epididymal maturation ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%